Design principles for developing online ethics resources - the outcome of holistic DBR process - Tammeleht, Anu (EDeR. Educational Design Research, 2022)
In various fields people need to make morally good decisions. At the same time, it is not very common in education to help people develop their ethics competencies of various fields. The current article gives an overview and outlines the outcomes of a holistic DBR process focusing on facilitation of the learning process to develop ethics competencies. Over the past 4 years an online research ethics resource has been under development by utilising DBR. The ultimate goal of DBR is to provide research-based design principles that would also be transferable into other contexts. While there is knowledge about effective strategies in ethics education and a variety of online resources have been developed, there are no design principles available that would enable creating ethics resources for different fields. The outcome of the current research is a set of design principles to help designing of ethics resources for various fields. Their transferability was tested and recommendations are provided for implementation.